Eruptive gingivitis during the eruption of a child's teeth: Gingivitis erupsi selama proses erupsi gigi anak - Putu Yetty Nugraha; I Gst Agung Ayu Hartini (Makassar Dental Journal, 2022)
Eruption gingivitis is an inflammation that occurs when the teeth erupt which is often associated with difficulty in tooth eruption and will subside after the teeth emerge in the oral cavity. The purpose of this study was to determine the process of gingivitis du-ring tooth eruption in children. The inflammatory process ofgingiva will show a change in the color of the gingiva such as be-coming red, swelling of the gingiva, and a distinctive surface texture. Eruption gingivitisassociated with the eruption of primary and permanent teeth, the accumulation of plaque, material alba and calculus due to poor oral hygiene, and the gingivalmargin did not receive adequate protection due to the contour of the crown during the early phase of eruption or active growth. The most effective way toprevent gingivitis is by controlling plaque regularly such as brushing teeth twice a day, using dental floss, using toothpaste that contains anti-plaque, maintaining oral health and visiting the dentist at least every 6 months.